Frequency and Yield of Postoperative Fever Evaluation - J. Fanning; R. A. Neuhoff; J. E. Brewer; T. Castaneda; M. P. Marcotte; R. L. Jacobson (Hindawi Limited, 1998)
Objective: In women undergoing major gynecologic surgery, we wish to determine the frequency and yield of blood culture, urine culture, and chest X-ray evaluation of postoperative fever.